PENGARUH MEDIA FUN LEARNING TERHADAP KEMAMPUAN MENGENAL HURUF HIJAIYAH ANAK USIA 4-5 TAHUN - Helpi Juntika; Rita Kurnia; Ria Novianti (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
This study aims to determine the effect of fun learning media on the ability to recognize hijaiyah letters of children aged 4-5 years in RA Azkiyah, Kuantan Singingi Regency. The subjects in this study were all kindergarten A students in RA Azkiyah, Kuantan Singingi Regency with a total of 27 children. The research method used, namely the Pretest-Posttest Design experiment to see the influence of fun learning media on the ability to recognize hijaiyah letters of children. The data analysis technique in this study is to use the t-test analysis using the SPSS statistical program series for window ver 23. From the analysis of the data, the tcount is 17,095, greater than ttable = 2,056 with sig 0,000 <0,05. The results of this study are there are significant differences in the ability to recognize hijaiyah letters of children before and after the use of fun learning media, it is concluded that there is an influence of Fun Learning media on the ability to recognize hijaiyah letters of children aged 4-5 years in RA Azkiyah Kuantan Singingi Regency by 48,29 %.